Developing Geometry Based Criterion Function Method for Predicting Porosity in LM6 Castings - A. Sata; N. Maheta; H. Khandelwal; S.K. Gautam (Archives of Foundry Engineering, 2025)
One of the major issues in the metal casting process that affects productivity and energy efficiency is porosity, especially when it comes to castings that are not made in accordance with Original Equipment Manufacturers (OEMs) specifications. Predictive method is crucial to solving this problem. Criterion function is a noteworthy empirical model that has been extensively studied in the literature. By taking into account important factors like cooling rate, thermal gradient and molten metal velocity during solidification, it provides predictive insights into the location and presence of porosity. It is essential to develop a criterion function that considers the impact of geometric variation on the occurrence of shrinkage porosity. In this paper, a geometry-based model has been proposed for LM6 castings using a standard shape with three T-joints for the prediction of shrinkage porosity. The findings suggest that the presence of joints significantly influences the formation of porosity and it was also observed that an increase in the length ratio leads to a higher occurrence of shrinkage porosity. This information is vital for designers as it guides them to maintain the length ratio within a defined range to prevent shrinkage porosity in T-junction castings.